2012
DOI: 10.1007/s12020-012-9757-1
|View full text |Cite
|
Sign up to set email alerts
|

Altered gene expression involved in insulin signaling pathway in type II diabetic osteoporosis rats model

Abstract: It is well established that both estrogen loss and type II diabetes mellitus (DMII) can impair bone metabolism, but whether estrogen loss exacerbates the effects of DMII is unclear. Therefore, we determined if ovariectomy (OVX) of rats on a long-term high-fat/sugar diet and injection of a low dose of streptozotocin (DMII) decreased bone mineral density (BMD) more than OVX or DMII alone. Bone insulin signaling is known to support bone metabolism; therefore, we also tested the hypothesis that OVX DMII rats (DOVX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…This widely-used model effectively mimics type 2 diabetes [1517]. As diabetes is mainly characterized by weight loss, high blood sugar and insulin resistance, we first confirmed that our rat model was a model of diabetes by examining the weights, blood sugar levels, and insulin sensitivity index (ISI) values of the animals.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…This widely-used model effectively mimics type 2 diabetes [1517]. As diabetes is mainly characterized by weight loss, high blood sugar and insulin resistance, we first confirmed that our rat model was a model of diabetes by examining the weights, blood sugar levels, and insulin sensitivity index (ISI) values of the animals.…”
Section: Resultsmentioning
confidence: 53%
“…However, in order to better simulate the results of diabetes mellitus (relatively reduced insulin secretion), we intraperitoneally injected rats with streptozotocin at a dose of 30 mg/kg. After 72 h, fasting plasma glucose of 7.8 mmol/L and reduced insulin sensitivity were observed, confirming the successful establishment of the model [15]. The rats not used for the model were fed a normal diet.…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…The rats were given an intraperitoneal injection of streptozotocin (STZ) at a dose of 30mg/kg. After 72 hours, fasting plasma glucose >7.8mmol/Land reduced insulin sensitivity were observed and the models were successfully established6. The rats not used for modeling were fed a normal diet.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study from our group showed that the expression of IGF1 and IRS1 is decreased in type 2 diabetic osteoporotic rats [26]. Liu HC et al found that the transfection of recombinant plasmid pEGFP-N1-IGF1 alleviated osteoporosis in ovariectomized rats [5].…”
mentioning
confidence: 87%